The BEI index: an approach for measuring the business environment in Africa - Topliceanu, Stefan Catalin; Sorcaru, Sergiu Lucian (Journal of Business Economics and Management, 2022)
Africa is becoming more and more attractive for trade and investment, while entrepreneurs are concerned about the quality of the business environment. This paper aims to analyze the Africa’s business environment and its dimensions in order to identify the most favorable destinations for starting a business. The methodology for this study includes research reviewing the existing literature and a quantitative approach based on a composite instrument. The results of the empirical study show that three regions have a favorable business environment for starting a business, while the most important dimensions of business are related to costs incurred, time and procedures required and trade aspects. First published online 04 April 2022